A descriptive anatomical study of the branching pattern of internal iliac artery in humans - P K Ramakrishnan; C D Selvarasu; M A Elezy (Wolters Kluwer Medknow Publications, 2012)
Background And Aims: Variations in the origin of the parietal branches of internal iliac artery are of great surgical and radiological importance. Very few studies regarding the variations in the origin of the branches of internal iliac artery have been reported from South India. The present study was carried out to investigate the sites of origin of the large parietal branches of the internal iliac artery in a sample Indian population from two Southern states. Materials And Methods: 5 pelvic halves of embalmed cadavers were dissected and observed for variations in the origins of superior gluteal, inferior gluteal, internal pudendal and obturator arteries. Results: Among the 50 pelvic halves studied, the origins of superior gluteal, inferior gluteal and internal pudendal arteries confirmed to a Type I arrangement on the Adachi scale in 30 cases (60%), a Type in pattern being found in 15 cases (30%) and a Type II pattern was seen in 4 cases (8 %). Type IV was less frequent and was seen in only one case( 2 %). The obturator artery arose directly from the anterior division of internal iliac artery in 40% of cases; in the rest of specimens, it arose as a branch from either the inferior gluteal-internal pudendal trunk or internal pudendal or superior gluteal or iliolumbar arteries. Conclusions: The data obtained from this study show that the branching pattern of internal iliac artery is subject to great variation, especially with regard to its four large parietal branches. These observations are important in diagnostic & interventional radiological procedures of this major artery as well as in pelvic surgery to minimize intra-operative blood loss.